Modified femtosecond laser inscription method for tailored grating sensors in encapsulated silica and low-loss polymer optical fibres - Kalli, Kyriacos; Lacraz, Amédéé; Theodosiou, Antreas; Kofinas, Marios (My University, 2016)
There is great interest in the development of flexible wavelength filters and optical fibre sensors, such as Bragg and superstructure gratings, grating arrays and chirped gratings in glass and polymer optical fibres. A major hurdle is the development of an inscription method that should offer flexibility and reliability and be generally applicable to all optical fibre types. With this in mind we have developed a novel femtosecond laser inscription method; plane-by-plane inscription, whereby a 3D-index change of controlled length across the fibre core, width along the fibre axis and depth is written into the optical fibre. We apply this method for the inscription of various grating types in coated silica and low- loss CYTOP polymer optical fibres. The plane-by-plane method allows for multiple and overlapping gratings in the fibre core. Moreover, we demonstrate that this novel fibre Bragg grating inscription technique can be used to modify and add versatility to an existing, encapsulated optical fibre pressure sensor. The femtosecond laser is operated in the green or the near infra-red, based on the material properties under laser modification.
Keywords: Bragg gratings; Femtosecond laser inscription; Optical fibre sensors; Polymer optical fibre